Multilayered Flap Technique: A Method for Delayed Closure of Giant Omphalocele. Issue 6 (June 2016) - Kruit, Anne Sophie; Al-Ani, Sami A.; Jester, Ingo; Jester, Andrea
Abstract : Abstract: Giant omphalocele is a rare, large abdominal wall defect in which the intra-abdominal organs herniate through the umbilical cord and are covered by a sac. Surgical management of giant omphalocele is challenging, and optimal treatment remains controversial. Two generally accepted treatment options are staged closure and delayed closure. Delayed closure takes place after a period of conservative treatment promoting omphalocele sac epithelialization. We present 3 patients treated by a delayed closure technique for ventral hernia repair. In this technique, the epithelialized omphalocele sac and peritoneum are elevated as flaps, which are used to reconstruct the abdominal wall in multiple layers.